2021
DOI: 10.3390/toxins13050344
|View full text |Cite
|
Sign up to set email alerts
|

Quo vadis Cardiac Glycoside Research?

Abstract: Cardiac glycosides (CGs), toxins well-known for numerous human and cattle poisoning, are natural compounds, the biosynthesis of which occurs in various plants and animals as a self-protective mechanism to prevent grazing and predation. Interestingly, some insect species can take advantage of the CG’s toxicity and by absorbing them, they are also protected from predation. The mechanism of action of CG´s toxicity is inhibition of Na+/K+-ATPase (the sodium-potassium pump, NKA), which disrupts the ionic homeostasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 138 publications
(163 reference statements)
0
18
0
Order By: Relevance
“…We found that more polar cardenolides are dominant in seeds, which contrasts with the more diverse and less polar composition in other tissues (Figure S1), the latter of which consistently showed greater inhibition against all insects. Structure-affinity relationships between cardenolides and the amino acid residues of the sodium pump seem to be driven by polar interactions of hydrogen bonds with the hydroxyl groups in the steroidal skeleton of cardenolides (Bejcek et al, 2021;Laursen et al, 2013). In other words, more polar compounds seem to have greater affinity to a more polar enzyme.…”
Section: Implications Of Plant Defence Tradeoffs and Relative Insect ...mentioning
confidence: 99%
“…We found that more polar cardenolides are dominant in seeds, which contrasts with the more diverse and less polar composition in other tissues (Figure S1), the latter of which consistently showed greater inhibition against all insects. Structure-affinity relationships between cardenolides and the amino acid residues of the sodium pump seem to be driven by polar interactions of hydrogen bonds with the hydroxyl groups in the steroidal skeleton of cardenolides (Bejcek et al, 2021;Laursen et al, 2013). In other words, more polar compounds seem to have greater affinity to a more polar enzyme.…”
Section: Implications Of Plant Defence Tradeoffs and Relative Insect ...mentioning
confidence: 99%
“…The expression of the NKA subunit in some cancer cells may be altered compared with healthy tissues (Mijatovic et al, 2007). Studies have shown that the antitumor effect of CTS is mainly through the non-transport function of NKA, that is, the activation of signal transduction function (Bejček et al, 2021). The specific antitumor efficacy and mechanism of action need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac glycosides are naturally occurring compounds found in plants and animals, where they serve as a defense mechanism . Cardiac glycosides have structures derived from the steroid skeleton . The skeleton typically consists of three 6-membered carbon rings and one 5-membered ring (Figure ), with a lactone ring at the C-17 position and a sugar moiety at C-3 .…”
Section: Discussionmentioning
confidence: 99%